Functional identification of two novel variants and a hypomorphic variant in ASS1 from patients with Citrullinemia type I - Liu, Jing; Wang, Zhongjie; Yan, Huiming; Teng, Yanling; Shi, Qingxin; Chen, Jing; Tang, Wanglan; Yu, Wenxian; Peng, Ying; Xi, Hui; Ma, Na; Liang, Desheng; et al. (Frontiers in Genetics, 2023)
Background: Citrullinemia type I (CTLN1) is a rare autosomal recessive inborn error of the urea cycle caused by mutations in the gene encoding the arginosuccinate synthetase (ASS1) enzyme. Classic CTLN1 often manifests with acute hyperammonemia and neurological symptoms. Molecular genetic testing is critical for patient diagnosis. Methods: Three unrelated families with clinically suspected CTLN1 were included in this study. Potential pathogenic variants were identified using whole exome sequencing (WES) and validated using Sanger sequencing. Western blotting, quantitative PCR, immunofluorescent staining, and ELISA were used to assess functional changes in candidate ASS1 variants. Results: Five variants were identified, two of which were novel, and one has been reported, but its pathogenicity was not validated. The novel variant c.649-651del (p.P217del) and the 5′UTR variant (c.-4C>T) resulted in a decrease in ASS1 expression at both the protein and transcription levels. The other novel variant, c.1048C>T (p.Q350*), showed a marked decrease in expression at the protein level, with the formation of truncated proteins but an increased transcription. Both c.649_651del (p.P217del) and c.1048C>T (p.Q350*) showed a highly significant reduction in enzyme activity, while c.-4C>T had no effect. Conclusion: We identified two novel variants and a hypomorphic non-coding variant in ASS1 and validated the pathogenicity using functional studies. Our findings contribute to expanding the spectrum of ASS1 variants and understanding the genotype-phenotype relationships of CTLN1.